ISOT position statement on the feasibility of an organ for transplantation from brain-dead deceased donors: a Delphi consensus - Manish R. Balwani; Vivek B. Kute; Jigar Shrimali; Bharat G. Jagiasi; Pradip Kumar Bhattacharya; Amit Pasari; Manoj Gumber; Sanjeev Gulati; Raj Kanwar Yadav; Shankar Prasad Nagaraju; Gomathy Narasimhan; Natarajan Gopalkrishnan; et al. (The Lancet Regional Health - Southeast Asia, 2025)
Summary: Organ shortage remains a critical challenge in India’s transplant landscape, despite established deceased donor organ transplantation (DDOT) programmes. Many potentially viable organs from brain-dead deceased donors (DBDs) are discarded due to uncertainties surrounding donor suitability in specific clinical scenarios. To address this gap, the Indian Society of Organ Transplantation (ISOT) convened a panel of national experts to develop a Delphi consensus statement aimed at guiding transplant professionals on the feasibility of organ donation from DBDs, particularly in complex or marginal donor situations. This position statement presents 19 consensus recommendations based on real-world clinical contexts such as extremes of age, acute kidney injury, infections (including HCV, HBV, HIV, tuberculosis, and tropical diseases), malignancy, diabetes, hypertension, and various surgical anomalies. The guidance is grounded in available literature, registry data, and extensive clinical experience, with the aim of expanding the DBD donor pool across Asia and improving access to transplantation for patients with end-stage organ failure. The consensus does not function as a formal clinical guideline but rather as a practical reference tool, acknowledging the limitations in India-specific data and the contextual differences from Western transplant settings. It encourages critical care and transplant teams to perform structured assessments of organ viability, apply ethical principles, and pursue informed consent in line with local regulations.